Meningkatkan Pemahaman dan Mengenal Islam Lebih Dekat melalui Bahasa Dakwah dalam Bingkai Digital - Harahap, Sartika Dewi; Harahap, Siti Rahma (Welfare : Jurnal Pengabdian Masyarakat, 2023)
Internet users around the world, especially in Indonesia, are dominated by Millennials. The search for identity and even religious knowledge, which is crucial, has made millennials choose the internet as a source of knowledge that is currently in demand. A preacher, through his official channels, spreads his da'wah through several social media platforms that are considered close to all levels of society. Youtube is one of the social media platforms that is in great demand by many millennial viewers who cannot be stopped today. This community service aims to explain the language of da'wah in a digital frame, which sees the YouTube phenomenon as a social media that conveys da'wah messages to get to know Islam better. Language, in a broad sense, is a mediator for conveying messages from speakers to listeners. The information that arrives can be full, half-full, or even lost. But for whatever reason, the delivery of Islamic da'wah messages cannot be underestimated. Especially in a digital frame that spreads like a virus. Millennials must get full information so they can get to know Islam more closely and be able to apply it in the right language and habits in their lives.